Neuropsychological impairment in bipolar I disorders in the euthymic state - Strijdom, Sonet Christina (My University, 2008)
ABSTRACT Over the last few years Bipolar Disorder has been associated with chronic neuropsychological deficits that remain even when episodes of depression, mania or hypomania remit. Furthermore Bipolar Disorder has been associated with progressive cognitive impairment, leading to the description of the illness as chronic and deteriorating, rather than as an illness with discreet episodes from which patients can fully recover. The results of neuropsychological studies have been criticized for methodological weaknesses however. The present study attempted to address these weaknesses. The aim was primarily to establish whether neuropsychological impairment exists in euthymic patients, and secondarily, to establish if neuropsychological functioning deteriorates with illness severity. Sixteen euthymic Bipolar I disordered patients were matched for age and sex to 16 controls and subjected to a battery of neuropsychological tests. Matched pair T-tests were used to identify if significant differences in neuropsychological functioning existed between the two groups. The ANOVA technique was used to determine if neuropsychological functioning deteriorated with illness severity. Markers of illness severity utilised in this study were number of depressive episodes, number of manic episodes, number of suicide attempts and number of hospitalisations. The results indicated that neuropsychological differences between the patient and control group were minimal and not clinically significant. The present study sample was medically and psychologically well managed and enjoyed good support structures and their neuropsychological functioning did not deteriorate with illness severity. It was concluded that the sample size and the nature of the sample selected could perhaps have affected the study outcome. It was therefore hypothesized that bipolar disorder is not a homogenous group and that protective factors may exist which affect the course and outcome of the illness. These protective factors should be the subject of further investigation as they are likely to significantly impact on the natural history of this disease process.
Keywords: bipolar disorder; impairment; euthymic; neuropsychological